Computational analysis of wax deposition in deep-water pipelines using nuclear techniques - Nalber Miranda Leite Nalber; Carlos Alberto Brayner de Oliveira Lira; Abel Gámez Rodriguez (Brazilian Journal of Radiation Sciences)
Wax deposition in oil pipelines is a problem that affects flow assurance because it restricts production and, in more extreme cases, causes pipeline blockages. This problem occurs more frequently in offshore environments, where most of Brazil's reservoirs are located and where the ocean temperature at great depths is around 5°C. Detecting the wax layer on the inside walls of pipelines at an early stage avoids unscheduled stoppages and major economic losses. Among the various methods and techniques found in the literature for monitoring wax deposition, nuclear techniques are distinguished by the fact that their use does not interfere with the physical integrity of the pipeline, by the non-intrusive and indirect (non-contact) mode of operation and, therefore, does not affect the oil transportation process. This paper presents a computational model using the Monte Carlo N-Particle 6 (MCNP6) code and the gamma radiation transmission profiling technique to detect the presence of wax on the inner walls of pipelines used for deepwater oil transportation. The results of this study show that the model can detect the presence of up to 5% wax (in relation to the internal radius of the pipeline) with an accuracy of 7.4% in pipelines used in deep waters.